Tawáº“Ä«f á¹¬arÄ«qah al-Ta'allum al-QÄ'im Ê¿alÄ al-MashrÅ«' fÄ« TadrÄ«s 'Ilmi al-BayÄn bi WÄsiá¹ah al-YÅ«tiub - Azman, Yusra; Chik, Abdul Rahman bin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The level of studentsâ€™ proficiency in rhetoric remains low from one of the questionnaires. The rhetoric material that the students learned was unclear, ineffective, frustrating, and boring. This is due to the difficulties of learning rhetoric, and the inappropriate method and tool for teaching students. As a result, the significance of this research stems from determining the efficacy of the YouTube method and the project-based learning method in terms of attracting students' attention and motivating them to participate in the teaching and learning process. This sample consists of six registered female students in Methods of Teaching Arabic as a Second Language subject. The study followed the inductive and applied descriptive approach, describing the concept of rhetoric, YouTube, and the project-based learning method scientifically in light of this phenomenon, and then applying this theory by conducting micro-teaching by employing YouTube in teaching rhetoric through the project-based learning method. The study concluded that the project-based learning method and the YouTube method are appropriate for teaching rhetoric because they draw students' attention to the lesson and stimulate their motivation to actively participate in the educational and learning process. The researcher noticed that the students interact well and participate in microteaching with positive and active participation, as they can understand more of the directions and lessons.Ø¥Ù†Ù‘ÙŽ Ù…Ø³ØªÙˆÙ‰ ÙƒÙØ§Ø¡Ø© Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø¹Ù„Ù… Ø§Ù„Ø¨ÙŠØ§Ù† Ù…Ù†Ø®ÙØ¶ Ù…Ù† Ø£ØØ¯ Ø§Ù„Ø§Ø³ØªØ¨ÙŠØ§Ù†. ÙƒØ§Ù†Øª Ù…Ø§Ø¯Ø© Ø§Ù„Ø¨Ù„Ø§ØºØ© Ø§Ù„ØªÙŠ ØªÙ… ØªØ¹Ù„Ù…Ù‡Ø§ Ù…Ù† Ù‚Ø¨Ù„ Ø§Ù„Ø·Ù„Ø§Ø¨ ØºÙŠØ± ÙˆØ§Ø¶ØØ© ÙˆØºÙŠØ± ÙØ¹Ø§Ù„Ø© ÙˆÙ…ØØ¨Ø·Ø© ÙˆÙ…Ù„Ù„Ø©. ÙÙ‡Ø°Ù‡ Ù„ÙˆØ¬ÙˆØ¯ Ø§Ù„ØµØ¹ÙˆØ¨Ø§Øª ÙÙŠ ØªØ¹Ù„Ù… Ø§Ù„Ø¨Ù„Ø§ØºØ© ÙˆÙƒØ°Ù„Ùƒ Ø§ÙØªÙ‚Ø§Ø± Ø§Ù„Ù…Ø¯Ø±Ù‘Ø³ÙŠÙ† Ø¥Ù„Ù‰ Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© ÙˆØ§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„Ù…Ù†Ø§Ø³Ø¨ØªÙŠÙ† Ù„ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ø·Ù„Ø§Ø¨. Ù„Ø°Ù„Ùƒ ØªÙƒÙ…Ù† Ø£Ù‡Ù…ÙŠØ© Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© ÙÙŠ ÙƒÙˆÙ†Ù‡Ø§ ØªÙ‡Ø¯Ù Ø¥Ù„Ù‰ Ù…Ø¹Ø±ÙØ© ÙØ§Ø¹Ù„ÙŠØ© ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ÙŠÙˆØªÙŠÙˆØ¨ ÙˆØ·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù‚Ø§Ø¦Ù… Ø¹Ù„Ù‰ Ø§Ù„Ù…Ø´Ø±ÙˆØ¹ Ù„ØªÙˆØ¸ÙŠÙÙ‡Ù…Ø§ ÙÙŠ ØªØ¯Ø±ÙŠØ³ Ø¹Ù„Ù… Ø§Ù„Ø¨ÙŠØ§Ù† ÙˆÙ„Ø¬Ø°Ø¨ Ø§Ù†ØªØ¨Ø§Ù‡ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙˆØ¥Ø«Ø§Ø±Ø© Ø¯Ø§ÙØ¹ÙŠØªÙ‡Ù… Ù†ØÙˆ Ø§Ù„Ù…Ø´Ø§Ø±ÙƒØ© ÙÙŠ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„ÙŠÙ… ÙˆØ§Ù„ØªØ¹Ù„Ù…. ØªÙ… Ø§Ø®ØªÙŠØ§Ø± Ø§Ù„Ø¹ÙŠÙ†Ø© ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© ÙˆÙ‡ÙŠ Ø³Øª Ø·Ø§Ù„Ø¨Ø§Øª Ø§Ù„Ù…Ø§Ø¬Ø³ØªÙŠØ± Ø§Ù„Ù„Ø§Ø¦ÙŠ Ø³Ø¬Ù„Ù†ÙŽ Ù…Ø§Ø¯Ø© Ø·Ø±Ù‚ ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨ÙˆØµÙÙ‡Ø§ Ù„ØºØ© Ø«Ø§Ù†ÙŠØ©. ÙˆØ§ØªØ¨Ø¹Øª Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ÙˆØµÙÙŠ Ø§Ù„Ø§Ø³ØªÙ‚Ø±Ø§Ø¦ÙŠ ÙˆØ§Ù„ØªØ·Ø¨ÙŠÙ‚ÙŠ ØÙŠØ« ØªØµÙ Ù…ÙÙ‡ÙˆÙ… Ø¹Ù„Ù… Ø§Ù„Ø¨ÙŠØ§Ù† ÙˆØ§Ù„ÙŠÙˆØªÙŠÙˆØ¨ ÙˆØ·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù‚Ø§Ø¦Ù… Ø¹Ù„Ù‰ Ø§Ù„Ù…Ø´Ø±ÙˆØ¹ ÙˆØµÙØ§ Ø¹Ù„Ù…ÙŠØ§ ÙÙŠ Ø¶ÙˆØ¡ Ù‡Ø°Ù‡ Ø§Ù„Ø¸Ø§Ù‡Ø±Ø©ØŒ Ø«Ù… ØªØ·Ø¨ÙŠÙ‚ Ù‡Ø°Ù‡ Ø§Ù„Ù†Ø¸Ø±ÙŠØ© Ù…Ù† Ø®Ù„Ø§Ù„ Ø¥Ø¬Ø±Ø§Ø¡ Ø§Ù„ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù…ØµØºØ± Ø¨ØªÙˆØ¸ÙŠÙ Ø§Ù„ÙŠÙˆØªÙŠÙˆØ¨ ÙÙŠ ØªØ¯Ø±ÙŠØ³ Ø¹Ù„Ù… Ø§Ù„Ø¨ÙŠØ§Ù† Ù…Ù† Ø®Ù„Ø§Ù„ Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù‚Ø§Ø¦Ù… Ø¹Ù„Ù‰ Ø§Ù„Ù…Ø´Ø±ÙˆØ¹.ÙˆØ§Ø³ØªÙ†ØªØ¬ Ø§Ù„Ø¨ØØ« Ø§Ù† Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù‚Ø§Ø¦Ù… Ø¹Ù„Ù‰ Ø§Ù„Ù…Ø´Ø±ÙˆØ¹ ÙˆÙˆØ³ÙŠÙ„Ø© Ø§Ù„ÙŠÙˆØªÙŠÙˆØ¨ Ù…Ù†Ø§Ø³Ø¨ØªØ§Ù† Ù„ØªÙˆØ¸ÙŠÙÙ‡Ù…Ø§ ÙÙŠ ØªØ¯Ø±ÙŠØ³ Ø¹Ù„Ù… Ø§Ù„Ø¨ÙŠØ§Ù†ØŒ Ø¥Ø° Ø¨Ù‡Ù…Ø§ ÙŠØªÙ… Ø¬Ø°Ø¨ Ø§Ù†ØªØ¨Ø§Ù‡ Â Ø§Ù„Ø·Ù„Ø§Ø¨ Ù†ØÙˆ Ø§Ù„Ø¯Ø±Ø³ ÙˆØ¥Ø«Ø§Ø±Ø© Ø¯Ø§ÙØ¹ÙŠØªÙ‡Ù… Ø¥Ù„Ù‰ Ø§Ù„Ù…Ø´Ø§Ø±ÙƒØ© Ø§Ù„ÙØ¹Ø§Ù„Ø© ÙÙŠ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„ÙŠÙ… ÙˆØ§Ù„ØªØ¹Ù„Ù…. ÙˆÙ„Ø§ØØ¸Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ø£Ù† Ø§Ù„Ø·Ù„Ø§Ø¨ ÙŠØªÙØ§Ø¹Ù„ÙˆÙ† ØªÙØ§Ø¹Ù„Ø§ Ø¬ÙŠØ¯Ø§ ÙˆÙŠØ´Ø§Ø±ÙƒÙˆÙ† ÙÙŠ Ø§Ù„ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù…ØµØºØ± Ù…Ø´Ø§Ø±ÙƒØ© Ø¥ÙŠØ¬Ø§Ø¨ÙŠØ© Ù†Ø´ÙŠØ·Ø© ØÙŠØ« Ø£Ù†Ù‡Ù… ÙŠØ³ØªØ·ÙŠØ¹ÙˆÙ† Ø§Ù„ÙÙ‡Ù… Ø¨Ø§Ù„ØªÙˆØ¬ÙŠÙ‡Ø§Øª ÙˆØ§Ù„Ø¯Ø±ÙˆØ³ Ø£ÙƒØ«Ø±.